Deep lobe tumors parotid - Castillo, Luis A (Cirugía del Uruguay, 1975)
The author studies the tumors of the deep lobe of the parotid gland, which are considerably less frequent thnn those nf the superficial lohe. Hs discusses the characteristics of those evolving toward the surface, as well as the ones evolving_ toward the depth. Out of 84 l'linical histories of parotid gland !umors ( 77 from the Ciínicas Hospital and 7 from ·the author), 46 corresponded to pleomorphous adenoma and 7 of them were located in the cieep lobe. It is suggested that tumors growing toward the oral cavity ( 3 cases of the series) origim1te, n0t in the deep lobe but in the pharingcal extension of the parotid g!and, in posterior accesory salivary glands or in aberrating salivary tissue. Considerations on the treatment are made.